Realizations of lossy and lossless capacitance multiplier using CFOAs - Ozer, Emre; Basak, Muhammed Emin; Kacar, Firat (ELSEVIER GMBH, 2020)
This paper presents a new Current Feedback Operational Amplifier (CFOA) based grounded capacitance multiplier (GCM) generic circuit. Lossy and lossless five GCM circuits were realized using this generic circuit. The lossless GCM circuit is studied in detail. The proposed lossless GCM includes two CFOAs, two resistors, and a grounded capacitor. Passive component matching conditions are not needed. In ideal and non-ideal conditions, the sensitivity analysis of the multiplication factor was performed. The effects of non-ideal conditions on the operating frequency range of the proposed GCM were investigated by mathematical analysis. The low-frequency performance has been improved by using a negative impedance converter (NIC). Functionality, time, and frequency domain analyzes were carried out using the LTspice simulation program. The voltage-mode band-pass filter application is included to demonstrate the usefulness of the circuit. The temperature dependence of the application example has been investigated. Monte Carlo analysis was carried out to verify the application example's robustness against the variation of the passive elements. In addition, a comparison with circuits in the literature is given to show the superiority of the proposed GCM.
Keywords: Capacitance multiplier; CFOA; AD844; Multiplication factor; 2ND-GENERATION CURRENT CONVEYOR; FLOATING INDUCTANCE; SIMULATOR; CIRCUITS; VOLTAGE; FDNR; CCII; TOPOLOGY; SERIES; Engineering; Telecommunications